How Placebo Needles Differ From Placebo Pills? - Chae, Younbyoung; Lee, Ye-Seul; Enck, Paul (Frontiers in Psychiatry, 2018)
Because acupuncture treatment is defined by the process of needles penetrating the body, placebo needles were originally developed with non-penetrating mechanisms. However, whether placebo needles are valid controls in acupuncture research is subject of an ongoing debate. The present review provides an overview of the characteristics of placebo needles and how they differ from placebo pills in two aspects: 1) physiological response and 2) blinding efficacy. We argue that placebo needles elicit physiological responses similar to real acupuncture and therefore provide similar clinical efficacy. We also demonstrate that this efficacy is further supported by ineffective blinding (even in acupuncture-naïve patients) which may lead to opposite guesses that will further enhances efficacy, as compared to no-treatment, e.g. with waiting list controls. Additionally, the manner in which placebo needles can exhibit therapeutic effects relative to placebo pills include enhanced touch sensations, direct stimulation of the somatosensory system and activation of multiple brain systems. We finally discuss alternative control strategies for the placebo effects in acupuncture therapy.